Social advertising an initial Brazilian position on the counterhegemonic possibilities of advertising communication based on the appropriation of mobile technologies - Saldanha, Patrícia (2018)
At the beginning of the re-examination of the typology of traditional marketing advertising based on classic authors of advertising communication, the two structuring types linked to the new “modi operandi” of the counter-hegemonic advertising practices that figure in social advertising, including community advertising, will be discussed. The idea is to contribute with the enrichment of the scientific discussion on communication in advertising and propaganda articulated to the recent consumption practices and made viable by mobile technologies.